Socio-epidemiological Profile of Family Planning Users at Abass Ndao Hospital Center from January to May 2023 - Coumba Ka; Boubacar Gueye; Alassane Barro; Cheikh Diop; Ndeye Sougou (Science Journal of Public Health, 2026)
Introduction: Family planning plays a major role in improving maternal and child health. Our objective was to determine the socio-epidemiological profile of family planning users at Abass NDAO Hospital Center. Materials and methods: This was a retrospective, descriptive and analytical study including all patients using family planning who had a record in the maternity ward of Abass Ndao Hospital Center from January 2023 to May 2023. Data were entered and analyzed using Microsoft Excel, Sphinx Plus version 4.5 and Stata MP 16.0 software. Results: We included 107 patients. The mean age of the patients was 29.5 years ±6.8. The 25-34 age group was the most represented (52.3%). The mean number of children was two (2). The majority of users had the status of “married women” (90.7%, n=97) and were educated (89.6%, n=95) with a strong representation of secondary and higher levels. About one quarter (n=27) of the patients were employees of the formal private sector, 23.4% (n=25) housewives and 21.5% (n=23) schoolgirls-students. The menstrual cycle was regular in 87.9%. There were more multiparous women (49.5%, n=53) than primiparous women (40.2%, n=43). The rate of high blood pressure, overweight and obesity was successively 12.1%, 29.4% and 25.5%. The main source of information on family planning was of medical origin through health workers (32.7%, n=35). The contraceptive methods most used were Depo injectable (41.1%, n=44) and Jadelle (27.1%, n=29). Conclusion: Our study was able to highlight the sociodemographic and clinical characteristics of family planning users, determine the planning methods most used in the maternity ward of ABASS NDAO Hospital Center, as well as the methods most frequently used.